Optimization of lipase-catalyzed synthesis of palm amino acid surfactant using response surface methodology (RSM) - Bidin H.; Basri M.; Radzi S.M.; Ariff A.; Abdul. Rahman R.N.Z.R.; Salleh A.B. (2024)
Indexed by Scopus